1957
DOI: 10.1042/bj0670015
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action of mercurial preparations on transport processes and the role of thiol groups in the cell membrane of renal tubular cells

Abstract: 1. A method is described for the accurate quantitative analysis of ketone bodies from small samples (0 1 ml.) of blood and urine.2. The method is based on the conversion of all ketone bodies into acetone, on the reaction of acetone with 2:4-dinitrophenylhydrazine and on subsequent colorimetric determination of acetone-2:4-dinitrophenylhydrazone in carbon tetrachloride.3. A combined reflux and distillation apparatus has been designed which ensures reproducibility in the estimation of P-hydroxybutyric acid and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1959
1959
1984
1984

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…This consideration would hold if C1 were passively distributed across the cell membrane. Bath to cell Cl concentration ratios between 1.5 and 4 have been reported (21,31,32,11) and we have obtained in preliminary experiments ratios between 1.3 and 2 at an external K concentration of 5.3 mmole/kg. These ratios are significantly lower than those expected from a passive distribution of Cl.…”
Section: The Possibility That Some K Is Bound Within the Cellsmentioning
confidence: 86%
“…This consideration would hold if C1 were passively distributed across the cell membrane. Bath to cell Cl concentration ratios between 1.5 and 4 have been reported (21,31,32,11) and we have obtained in preliminary experiments ratios between 1.3 and 2 at an external K concentration of 5.3 mmole/kg. These ratios are significantly lower than those expected from a passive distribution of Cl.…”
Section: The Possibility That Some K Is Bound Within the Cellsmentioning
confidence: 86%
“…It is also deposited in the liver, muscles, and bones (Dathan, 1954;Polson and Tattersall, 1959b). Mercury has a specific affinity for sulphydryl groups, including those concerned with transport mechanisms across the renal tubular basement membrane (Kleinzeller and Cort, 1957). Burston, Darmady, and Stranack (1958) showed that damage to the convoluted tubules, both proximal and distal, was the salient feature of the acute nephrotoxicity of mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Since mercury poisoning probably inhibits active sodium transport (23), some other driving force must have been responsible for passive movement of water across the epithelium. The only other force of sufficient magnitude to accomplish this is the colloidal oncotic pressure of the peritubular capillary blood, which is equivalent to approximately 35 cm of water (2).…”
Section: Discussionmentioning
confidence: 99%